Pelatihan Ilmu Kelistrikan Di Lingkungan Pondok Pesantren An-Nur Ciseeng - Fadly Nur Azzidane; Zalfa Rafandra Kusuma; Nurul Huluq; Jamal A Rachman; Seflahir Dinata (Pusmedia Group Indonesia, 2026)
Safety in the use and installation of electrical systems is a critical aspect in preventing electrical accidents and fires caused by malfunctions in the electrical system. However, the use of electrical energy at the An-Nur Ciseeng Islamic Boarding School has not been accompanied by an adequate understanding of electrical safety, energy efficiency, and the use of simple electrical technology as a backup energy source. The identified issues include low awareness of energy-efficient electricity use, a lack of knowledge regarding the maintenance of electrical installations, and limited skills in utilizing and assembling simple electrical systems. This community service activity aims to improve the students’ understanding and skills regarding electrical safety and the application of simple electrical technology. The implementation method used the Participatory Action Research (PAR) approach, which includes the mapping, planning, implementation, and evaluation stages. The program was conducted through a combination of 30% theoretical instruction and 70% hands-on practice, covering an introduction to electrical fundamentals, series-parallel circuits, soldering techniques, the construction of emergency lights, and training in simple electrical installation and repair. Evaluation was conducted using pre-tests, post-tests, and assessments of practical performance. The results of the activity showed an improvement in the students’ understanding and skills in the field of electricity, as evidenced by a 35% increase in their average scores following the training. In addition, all participant groups successfully produced simple emergency lights and were able to apply safety principles in electrical work. This activity made a positive contribution to improving the students’ electrical literacy, technical skills, and awareness of the safe, effective, and efficient use of electrical energy.